KONSEP DESAIN KURSI PENUMPANG PESAWAT KELAS EKONOMI DI INDONESIA - Erwin Nurrizki Tanjung; Agus Edy Pramono (Recent in Engineering Science and Technology, 2026)
Aircraft seat bench concept is designed with three adjustment points—armrests, backrest, and the middle of the backrest—and is equipped with a headrest to support the passenger’s head and neck comfort. These features aim to enhance passenger comfort without limiting the movement space of neighboring passengers, which is often a concern in conventional aircraft seat designs. To reduce production costs and maintain efficiency, the materials used are commonly available in the market. The seat frame is made of lightweight yet strong aluminum, the seat cushion and backrest utilize polyurethane (PU) foam for comfort, and the outer covering uses synthetic leather, which is affordable yet visually appealing. This material selection facilitates mass production and simplifies maintenance. Structural testing using Autodesk Inventor software indicates that the design is safe for use, achieving a safety factor of 3.62, which signifies strong resistance to stress and load during usage.